IMPLEMENTASI BEBERAPA UJI KENORMALAN OMNIBUS DENGAN PERANGKAT LUNAK R - SUMARJAYA, I WAYAN (Jurnal Matematika; Vol 1 No 1 (2010)DO - 10.24843/JMAT.2010.v01.i01.p06)
An omnibus normality test is a normality test that can give additional information about nonnormality or other deviation from normality through the skewness and the kurtosis coefficients. The aim of this research is to implement the omnibus D’Agostino-Pearson K2 test and modified Jarque-Bera test statistic using R software.
Keywords: omnibus normality test, D’Agostino-Pearson test, modified Jarque-Bera.